ANALISIS PENGARUH JARAK KAMPUH HASIL PENGELASAN BAJA SS400 TERHADAP SIFAT MEKANIK MATERIAL MENGGUNAKAN METODE GMAW - Indrayani, Novi Laura; Oktadinata, Herry; Suteja, Ito (Jurnal Ilmiah Teknik Mesin, 2020)
Welding techniques have been used extensively in the construction field because welding techniques are a simpler method in the process of connecting steel than using bolts or rivets. Factors that influence the quality of welding results include distance of the seam. The seam distance can affect the increase in heat input value because the wider the seam distance the more filler metal will be used. The purpose of this study was to determine how the effect of variations in the distance of the seam to the mechanical properties of SS400 steel welding material using the GMAW method. SS400 steel welding welding position 2G with variations in the root gap distance of 0 mm, 2 mm and 4 mm using the GMAW method with a type of protective gas 82% Ar + 18% CO2 and ESAB ER70S-6 type welding wire. Single v butt joint type with a seam angle of 60o and 12 mm thick material. In this study several tests were conducted including distortion testing, non-destructive test, tensile, chemical composition, hardness and microstructure observation. The highest distortion test results obtained at a root gap of 4 mm seam, non-destructive test results showed no welding defects in the upper surface of the weld, the optimal tensile testing results were obtained on a sample root gap of 2 mm with a tensile strength value of 413 MPa and fractures that occurred in the base area metal. The highest hardness test results were obtained at a sample root gap of 0 mm ap with a value of 235 HV and the lowest hardness obtained at a root gap of 4 mm with a value of 209 HV.